2017
DOI: 10.1007/s13311-016-0489-4
|View full text |Cite
|
Sign up to set email alerts
|

EGAR, A Food Protein-Derived Tetrapeptide, Reduces Seizure Activity in Pentylenetetrazole-Induced Epilepsy Models Through α-Amino-3-Hydroxy-5-Methyl-4-Isoxazole Propionate Receptors

Abstract: A primary pathogeny of epilepsy is excessive activation of α-amino-3-hydroxy-5-methyl-4-isoxazole propionate receptors (AMPARs). To find potential molecules to inhibit AMPARs, high-throughput screening was performed in a library of tetrapeptides in silico. Computational results suggest that some tetrapeptides bind stably to the AMPAR. We aligned these sequences of tetrapeptide candidates with those from in vitro digestion of the trout skin protein. Among salmon-derived products, Glu-Gly-Ala-Arg (EGAR) showed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 60 publications
(66 reference statements)
0
4
0
Order By: Relevance
“…More than a single proteolytic enzyme (whether purified or crude) can be used to hydrolyze the protein to produce the hydrolysate containing short peptide sequences. However, addition of the enzymes (whether simultaneously or sequentially) would depend on the optimal pH and temperature of the enzymes [ 14 , 15 , 16 , 17 ]. Though no specific proteolytic enzymes are known to produce specific bioactive peptides in foods, subtilisin hydrolysis tends to yield low molecular weight peptides some of which are bioactive.…”
Section: Production and Processing Of Food Protein-derived Bioactimentioning
confidence: 99%
“…More than a single proteolytic enzyme (whether purified or crude) can be used to hydrolyze the protein to produce the hydrolysate containing short peptide sequences. However, addition of the enzymes (whether simultaneously or sequentially) would depend on the optimal pH and temperature of the enzymes [ 14 , 15 , 16 , 17 ]. Though no specific proteolytic enzymes are known to produce specific bioactive peptides in foods, subtilisin hydrolysis tends to yield low molecular weight peptides some of which are bioactive.…”
Section: Production and Processing Of Food Protein-derived Bioactimentioning
confidence: 99%
“…By mediating excitatory synaptic transmission and enhancing the excitatory postsynaptic current, AMPARs ultimately participate in the onset of epilepsy and development ( Jaremko et al, 2017 ; Widagdo et al, 2017 ; Joshi et al, 2018 ). Thus it can be seen AMPAR complexes play a major role in the pathogenesis and development of epilepsy ( Mayer, 2016 ; Adotevi and Leitch, 2017 ; Cai et al, 2017 ). Proteomics and mass spectrometry analysis had been revealed that OLFM3 may be involved in the formation of AMPAR complexes ( Schwenk et al, 2012 ; Shanks et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, after EGAR treatment, epileptic seizures in mice models are shorter and lighter; EGAR shows potential as an antiepileptic drug targeting AMPAR inhibition. 41 Walnut peptide has shown a significant neuroprotective effect on three different mouse epileptic seizure models. Further research shows that walnut peptides play an anticonvulsant role by regulating benzodiazepine receptors (GABA, an ion channel).…”
Section: Anxiety and Depressionmentioning
confidence: 99%
“…The salmon skin peptide (EGAR) selectively inhibits synaptic transmission mediated by α-amino-3-hydroxy-5-methyl-4-isoxazole propylene receptor (AMPAR) overactivation in vitro, without affecting the electrophysiological characteristics of hippocampal vertebral neurons, while reducing neuronal peaks in epileptic seizure models. In addition, after EGAR treatment, epileptic seizures in mice models are shorter and lighter; EGAR shows potential as an antiepileptic drug targeting AMPAR inhibition . Walnut peptide has shown a significant neuroprotective effect on three different mouse epileptic seizure models.…”
Section: Neuroprotective Effects Of Bioactive Peptides In Cns Diseasesmentioning
confidence: 99%